Is there an affective neuroscience of spirituality? The development and validation of the OCEANic feelings scale - Schmautz, Beate; Fuchshuber, Jürgen; Andres, Deborah; Prandstätter, Theresa; Roithmeier, Lisa; Freund, Anton; Schwerdtfeger, Andreas; Unterrainer, Human-Friedrich (Frontiers in Human Neuroscience, 2024)
Background: Oceanic feelings represent a phenomenological structure of affective sensations that characteristically involve feelings of self-dissolution and feelings of unity and transcendence. This study presents the preliminary version of a self-report instrument to measure individual dispositions towards oceanic feelings in order to enable further research within the concept of primary emotions postulated by Jaak Panksepp.A first version of the questionnaire was applied to a total sample of 926 German-speaking adults of the general population. After performing item analysis and principal component analysis (PCA) in a first study (N = 300), the questionnaire was shortened. In a second study (N = 626), confirmatory factor analysis (CFA) was conducted and emerged scales were related to the already established instruments for the assessment of primary emotions (BANPS-GL) and Big Five personality traits (BFI-44).The OCEANic scale exhibited reliabilities ranging from Cronbach's α = .82 (positive) to α = .88 (negative) and plausible correlations with behavioral traits related to the seven affective neurobiological systems (ANGER, FEAR, CARE, SEEK, PLAY, SADNESS and LUST) as well as with personality factors measured by the Big Five Inventory. For CFA, a bifactorial model with an overall factor demonstrated good fit: RMSEA = .